Kontribusi pajak daerah dalam peningkatan pendapatan asli daerah (Studi pada Dinas Pendapatan Daerah Kota Manado) - Budie, Sheva Angely Bianca; Gamaliel , Hendrik; Sardjono , Olivia Y. M. (Yayasan Widyantara Nawasena Raharja, 2025)
Regional tax is one of the main pillars of local revenue (PAD) that supports the implementation of regional autonomy. However, the contribution of each type of tax may vary depending on the effectiveness of collection and local economic conditions. This study aims to analyze the contribution of restaurant tax, entertainment tax, advertising tax, and parking tax to regional tax revenue, as well as the role of regional tax revenue in supporting Manado City's PAD during 2020–2023. The research employed a descriptive quantitative approach, combining primary data from interviews with the Regional Revenue Agency and secondary data from official tax reports. The results show that restaurant, entertainment, and parking taxes tended to increase their contribution, while advertising tax showed a declining trend. Furthermore, regional taxes contributed an average of 98% to PAD, confirming their dominant role as the primary source of local fiscal capacity. These findings strengthen the theoretical perspective that regional taxes are a strategic instrument for regional autonomy, while practically suggesting the need to improve supervision, adopt digital tax systems, and diversify the tax base to maintain revenue sustainability.